AFRICAN FOOTBALLERS IN EUROPE migration, community, and give back behaviours. - Acheampong, Ernest Nti.; Bouhaouala, Malek; Raspaud, Michel ([S.l.] : ROUTLEDGE, 2019)
African Footballers in Europe traces the social and economic evolution of African football and examines the strategies and resources that players mobilise in their migrations, with a particular focus on Give Back Behaviours' (how players contribute to their countries or communities of origin). It shines new light on contemporary migrations, labour markets in sport, and processes of development in Africa. Using a multidisciplinary approach and Weberian methodology to analyse players' 'Give Back' behaviour, the book highlights the complex rationale behind this behaviour, based on a combination of social, cultural, and economic elements. It features interviews with former and current African professional players, providing a vivid picture of the role of communities in players' migration projects, the allure of the European football market, and investment initiatives that can contribute to local and regional development. This is a vital read for academics, researchers, and students of sport sciences, sociology of sport, sport management, sociology, geography, political sciences, management, sociology of Africa, migration studies, sociology of the labour market, and economic sociology. It is also an important resource for professional organisations, NGOs, football agents, football administrators, federations, confederations, and governments.
OCLC-licensed vendor bibliographic record.
Keywords: Soccer -- Africa; Soccer players -- Africa; Soccer players -- Europe; Africans -- Europe; SPORTS & RECREATION / General; SPORTS & RECREATION / Soccer; SPORTS & RECREATION / Sociology of Sports